2010
DOI: 10.1016/j.ejso.2009.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative tumor cell dissemination in patients with primary or metastatic colorectal cancer

Abstract: Introduction: Although there is general correlation between the TNM stage of colorectal cancer (CRC) and its prognosis, there is often significant variability of tumor behaviour and individual patient outcome, which is unaccounted for by pathologic factors alone. Our aim was to estimate perioperative tumor cell dissemination in patients with primary or CRC liver metastases as a possible factor influencing the outcome. Methods: Forty patients were prospectively enrolled in the study from the year 2007 to 2008. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…Earlier-stage diseases, small sample size, possibly technical difference, and timing of CD133 mRNA acquisition (preoperative vs postoperative) may explain the differences why CD133 mRNA was not prognostic in the current study. Our study included stage IV colorectal cancer patients who may shed more CD133+ circulating tumor cells [74]. Quantification of CD133+ cells using with flow cytometry or RT-PCR alone or in conjunction with other biomarkers may be useful to monitor treatment response to antiangiogenic agents including sorafenib plus erlotinib [75], and bevacizumab [76], and chemotherapy plus antiangiogenic agents [77].…”
Section: Prognostic Values Of Cd133 Expression In Cancer and In Peripmentioning
confidence: 99%
“…Earlier-stage diseases, small sample size, possibly technical difference, and timing of CD133 mRNA acquisition (preoperative vs postoperative) may explain the differences why CD133 mRNA was not prognostic in the current study. Our study included stage IV colorectal cancer patients who may shed more CD133+ circulating tumor cells [74]. Quantification of CD133+ cells using with flow cytometry or RT-PCR alone or in conjunction with other biomarkers may be useful to monitor treatment response to antiangiogenic agents including sorafenib plus erlotinib [75], and bevacizumab [76], and chemotherapy plus antiangiogenic agents [77].…”
Section: Prognostic Values Of Cd133 Expression In Cancer and In Peripmentioning
confidence: 99%
“…The probability of developing distant metastases is thought to be correlated with the number of CTCs in the blood. However, existing reports in the literature are varied and some are conflicting (9)(10)(11)(12). Notably, most studies addressing the roles of CTCs in metastasis were conducted in stage IV patients who had already developed distant metastases (13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…Mice were then treated on days 12,15,19,22,26,29, and 33. For treatment with recombinant murine granulocyte macrophage colony-stimulating factor (rGM-CSF), mice were subjected to intraperitoneal injection with 5 mg/ kg rGM-CSF protein (415-ML; R&D Systems) or the same amount of a control PBS solution on the days indicated.…”
Section: Mouse Blood Sampling and Analysesmentioning
confidence: 99%
“…This study found that postoperative relapse was strongly correlated with laparotomy versus laparoscopic surgery, lymph node metastases, as well as CTC levels if elevated at both preand postoperative time points (Lu et al, 2011). In contrast, another study reported no statistically significant difference of the CD45 -/CK + tumor cell count in the blood at time of surgical incision, after tumor resection and at the end of operation (Tralhão et al, 2010). A similar result was published by Wind et al for the respective type of operative procedures, revealing that the cumulative percentage of samples containing CTCs was significantly higher during open surgery as compared to the laparoscopic approach (Wind et al, 2009).…”
Section: Surgery and Tumor Cell Disseminationmentioning
confidence: 56%